PENGARUH TEKNIK RELAKSASI GENGGAM JARI TERHADAP PENURUNAN INTENSITAS NYERI PADA PASIEN POST OPERASI LAPARATOMI - Pinandita, Iin; Purwanti, Ery; Utoyo, Bambang (LPPM STIKES MUHAMMADIYAH GOMBONG, 2012)
Pain is the most common reason for people to seek health careand is one of the most common complaint of patients after a surgery. Tocope with pain, pain management is needed that includes nonpharmacologicaland pharmacological management. Hand grip relaxationtechnique is one of non-pharmacological techniques to emotions whichcan cause pain increase for the post laparotomy patients. The aim of thisstudy is to find out the influence of hand grip Relaxation Technique toDecrease pain Intensity of Post Laparatomy Patients in PKUMuhammadiyah Gombong Hospital.This research method is a Quasiexperimentwith the pre test-post test approach with control groupdesign. The study was conducted in PKU Muhammadiyah GombongHospital with 34 respondents using purposive sampling based oninclusion and exclusion criteria.The paired t-test shows that mean pain intensity in theexperimental group pre-test = 6.64 and the mean postoperative painintensity of the test = 4.88. While the mean pain intensity in the controlgroup pre test = 6.58 and the mean postoperative pain intensity test =6.47. The average difference of pre and post test in the experimentalgroup =1.764, whereas the average difference of the pre and post test inthe control group = 0.117. Based on independent t-test results, it wasobtained significance (p), with p-value = 0.000, where the value (p <0.05),meaning that there is an influence of hand grip Relaxation Technique toDecrease pain Intensity of Post Laparatomy Patients in PKUMuhammadiyah Gombong Hospital.Keywords Hand grip relaxation technique, Pain, Post Laparatomy